Deploying hybrid quantum-secured infrastructure for applications: When quantum and post-quantum can work together - Fedorov, Aleksey K. (Frontiers in Quantum Science and Technology, 2023)
The vast majority of currently used cryptographic tools for protecting data are based on cer- tain computational assumptions, which makes them vulnerable with respect to technological and algorithmic developments, such as quantum computing. Existing options to counter this potential threat include, first of all, quantum key distribution, whose security is based on the laws of quan- tum physics and, thus, it is proven to be secure against any unforeseen technological developments. The second approach is to switch to post-quantum cryptography, which is a set of cryptographic primitives that are believed to be secure even agains attacks with both classical and quantum com- puting technologies. In this perspective, a recent progress in the deployment of the quantum-secured infrastructure based on quantum key distribution, post-quantum cryptography, and their combina- tions, is reviewed. Various directions in the further development of the full-stack quantum-secured infrastructure are indicated. Distributed applications, such as blockchains and distributed ledgers, are also covered.